Pyrolysis of Carbonaceous Particles and Properties of Carbonaceous-g-Poly (acrylic acid-co-acrylamide) Superabsorbent Polymer for Agricultural Applications - Suriati, Ghazali; Saidatul Shima, Jamari; Tan, Kui May (EDP Sciences, 2016)
Utilisation of fertilizer and water are very important in determining the production of agriculture nowadays. The excessive use of fertilizer in plantation somehow could leads to environmental pollution. The present study reported a synthesis of controlled release water retention (CRWR) fertilizer coating with superabsorbent polymer (SAPs). Superabsorbent polymer (SAPs) are polymers that have ability to absorb and retain large amounts of water relative to their own mass. The presence of coating layer of SAPs on fertilizer granules was believed could reduce excessive used of fertilizer by controlling their dissolution rates and also reduce the environmental pollution. In this study, the effect on the addition of carbonaceous filler in SAPs on the water absorbency was also be compared with control SAPs (without carbonaceous particles). In this study, the carbonaceous filler were obtained from pyrolysis process of empty fruit bunch (EFB) biomass. The synthesized of SAPs and carbonaceous-SAPs were carried out via solution polymerization technique by using monomer of poly(acrylic acid) (AA), acrylamide (AM), cross linker, methylene bisacrylamide (MBA) and initiator, ammonium peroxodisulfate (APS) that partially neutralized with sodium hydroxide (NaOH). The CRWR fertilizer was later be prepared by coated the fertilizer granule with SAPs and carbonaceous-SAPs. The water absorbency, morphology and the bonding formation of both CRWR fertilizer were investigated by using tea-beg method, Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectrophotometer (FTIR), respectively. Moreover, the water retention studies was conducted in order to investigate the efficiency of CRWR coated with SAP and carbonaceous-SAP in retaining the water content in different soil (organic and top soil). Based on the results, the CRWR fertilizer that was coated with carbonaceous-SAP had higher water absorbency value than the CRWR fertilizer without carbonaceous-SAP. Meanwhile, 1 wt % CRWR fertilizer in organic soil gave higher water retention ability compared with 1 wt % CRWR fertilizer in top soil. In conclusion, CRWR fertilizer coated with carbonaceous filler gave a significant influence on the water absorbency and in controlling the nutrients release rate as well as function as water retention in soil.